Effects of Recombination Zone Formation on Optical Path Length and Device Performance in Blue Phosphorescent Organic Light-Emitting Diodes with Quantum Well Structure. (1st January 2016) - Rhee, Sang Ho; Kim, Sung Hyun; Ryu, Seung Yoon
Abstract : The effects of location and density in triplet exciton formation on the device performance were systematically investigated by the variation of quantum well (QW) structure in blue phosphorescent organic light-emitting diodes. The hole transporting material of 1, 1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC) as an interlayer was sandwiched between front emitting layer (EML) and rear EML for the construction of QW structure. The variation of the number of the QW unit induces the different exciton formation in recombination zone (RZ) in which the change of exciton density in the QW structure gives rise to the different optical path length and micro-cavity effect of the EL spectra. As the number of the QW unit increases, the corresponding EL spectrum is blue-shifted. It is originated that the exciton density in the front EML increases and the corresponding optical path length is shorten from the EML to the anode. However, the RZ formation in the single EML without QW structure is widened and red-shifted with increasing the EML thickness because the width of the RZ increases toward to the cathode and the length of optical path is expanded from the anode. In addition, the device having 2 units of QW structure in the EML shows the highest device performance of current efficiency, due to the good charge balance and avoiding the serious triplet exciton quenching by the interlayer. The current efficiency of 11.7 cd/A (from 11.7 to 7.3), power efficiency of 5.5 lm/W (from 5.5 to 3.4), and the operation voltage of 9.7 V at 5000 cd/m 2 were presented for 2 unit QW, while the current efficiency of 9.4 cd/A (from 9.4 to 4.7), power efficiency of 5.9 lm/W (from 5.9 to 1.6) and the operation voltage of 7.1 V at 5000 cd/m 2 were suggested for 1 unit QW, both showing relatively large efficiency roll-off.